Gambaran Aktivitas Penyakit dengan Indeks Basmi pada Pasien Spondiloartritis di Poli Reumatologi RSUD Dr. Soetomo Surabaya - Raisha Putri Azzahra; Yuliasih Yuliasih; Lukas Widhiyanto; Awalia Awalia (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Spondyloarthritis (SpA) is a group of inflammatory diseases affecting the peripheral and axial joints, with a significant impact on patients’ quality of life and productivity. Diagnosis and evaluation of disease activity are often hindered by non-specific symptoms. This study aims to evaluate SpA disease activity using the Bath Ankylosing Spondylitis Metrology Index (BASMI) at Dr. Soetomo General Hospital, Surabaya. This was a descriptive cross-sectional study using consecutive sampling. A total of 50 SpA patients were examined, with 45 meeting the inclusion criteria. Data were obtained through measurement of five BASMI components: tragus to wall distance, lumbar side flexion, modified Schober’s test, cervical rotation, and intermalleolar distance. The majority of patients were aged 17–60 years, with a mean age of 41.83 years, and were predominantly female (88.89%). Measurements showed that most patients had a tragus-to-wall distance of 10–12.9 cm, lumbar side flexion of >20 cm, modified Schober’s test of >7 cm, cervical rotation ranging from 59.6° to 68°, and intermalleolar distance between 70–79.9 cm and 50–59.9 cm. The total BASMI scores ranged from 0.4 to 3.8, with the majority falling within the range of 2–2.99. There is a variation in the degree of axial movement limitation among SpA patients as measured by BASMI, which can serve as a practical evaluation tool in clinical practice. In the assessment of each BASMI component, the average score showed a tragus-to-wall distance of 11.74 (+/- 3.46) cm, lumbar side flexion of 25.73 (+/- 8.94) cm, Modified Schober's test of 7.11 (+/- 2.27) cm, Cervical Rotation of 64.4 (+/- 11.5)°, intermalleolar distance of 64.69 (+/- 18.13) cm. In general, the results of BASMI measurements in the subjects showed limitations in axial and peripheral movements, which reflected the activity of SpA disease in this population.